Augmented reality storytelling: a transmedia exploration - Santano, Delas *; Thwaites, Harold * (IEEE, 2018)
This research paper discusses the implementation of augmented reality in transmedia storytelling. The innovation was applied on the subject matter of culture and heritage. A range of content was designed for augmented reality distribution for the 2 research-creation output from the projects. The paper will discuss the consideration of the chosen content for AR distribution, its production design and lastly its limitation on the type of content that was chosen.